THE DEVELOPMENT OF BADMINTON OVERHEAD LOB MODEL THROUGH VARIOUS EXERCISES ON NOVICE ATHLETES OF PB. ANUGRAH PADANG SELASA PALEMBANG - Nobery, Aditya (Sriwijaya University Learning and Education International Conference, 2018)
The purpose of this study : (1) develop the badminton overhead lob model through various exercise on novice athlete, (2) acknowledge the effectiveness of the overhead lob model. Brog and Gall model is used for this study. The subject is 10 novice athletes of PB. Anugrah Padang Selasa Palembang. Questionnaries used as the instrument of this study to collect data at the stage as follows (1) Analysis of Necessity (2) The Expert Evaluation (Initial Product Evaluation) (3) The Limited Testing (small group testing) (4) The Main Testing. The Overhead Lob is conducted 3 times of experiments in the effectiveness testing to get the best value. In order to get the result of model effectiveness, used the statistic t-test, re-observation with a significant level α = 0,05. Based on the results, concluded that : (1) Trainers need the overhead lob development through various exercise (2) This product is effective to be implemented by the trainers in overhead lob practice. (3) It is proven empirically that the development of badminton overhead lob model through various exercise on novice athletes of PB. Anugrah Padang Selasa Palembang is very effective based on the result.